The Impact Of Knowledge Share On Employee Performance: The Role Of Gender - Baidun, Akhmad; Karyono, Karyono; Solapari, Nuryati; Krishernawan, Indra (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to determine the extent to which knowledge sharing influences performance employee And How gender can moderate connection between knowledge sharing And performance employee. Study This use method collection data quantitative with collection data field use method questionnaire Which shared direct to employee part marketing PT. Kahatex. Analysis data using the Partial Least Square (PLS) approach. The research results show that knowledge sharing has a positive and significant effect on employee performance and gender has not been tested capable of acting as a moderating variable between the effects of knowledge sharing to performance employee. Keywords: Knowledge Sharing , gender, Performance Employee